Emotional Intelligence And Spiritual Intelligence On Employee Performance With Organizational Commitment As An Intervening Variable And Moderated By Islamic Spiritual Intelligence Using The Systematic Literature Review Method - Febry Rosady; Hwihanus Hwihanus; Muhammad Bayu; Darmono Darmono (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to evaluate the effect of emotional and spiritual intelligence on employee performance with organizational commitment as an intervening variable, as well as Islamic spiritual intelligence as a moderating variable. It is important to conduct in-depth empirical research to test the assumptions and confirm the relationship between emotional intelligence, spiritual intelligence, employee performance, organizational commitment, and moderation of Islamic spiritual intelligence. The methodology in this study is a systematic literature review (SLR). As for research methods such as survey studies or experimental research can be used to test hypotheses and perform statistical analysis as well as a deeper understanding of the relationship between KE, KS, employee performance, organizational commitment,